Critical Pedagogy in Social Studies Education: Empowering Students Through Democratic Dialogue - Damir Pada; Muhammad Rusli; Jumadi Jumadi (Journal La Edusci, 2025)
This study explores how critical pedagogical practices are enacted and experienced within a social studies classroom through a qualitative case study approach. Drawing on critical pedagogy, the study examines how dialogical teaching shapes students’ participation, meaning making, and emerging critical awareness over time. The classroom is treated as a bounded case, enabling close attention to pedagogical processes as they unfold in everyday instructional practice. Data were generated through classroom observations, in depth interviews with the teacher and students, focus group discussions, and students’ reflective journals collected over one academic year. An interpretative analysis was conducted to trace patterns of interaction, shifts in classroom dialogue, and participants’ evolving understandings of learning. The study does not aim for generalization but seeks to develop contextual and process oriented insights. Findings show that critical pedagogy functioned as a relational and evolving practice rather than a fixed method. Classroom dialogue gradually shifted from teacher centered exchanges toward more collective meaning making, with students becoming more willing to question assumptions, engage with multiple perspectives, and connect social studies content to broader social issues. Moments of tension and emotional discomfort emerged as integral to learning, supporting reflection and deeper engagement rather than hindering instruction. This study contributes to critical pedagogy scholarship by demonstrating how dialogical practices develop over time within a single classroom and by highlighting the value of qualitative case study methods for capturing the relational and affective dimensions of critical learning.